2023
DOI: 10.1002/ecm.1568
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐dependent diversity–biomass relationships can be driven by tree mycorrhizal association and soil fertility

Abstract: Diversity–biomass relationships (DBRs) often vary with spatial scale in terrestrial ecosystems, but the mechanisms driving these scale‐dependent patterns remain unclear, especially for highly heterogeneous forest ecosystems. This study explores how mutualistic associations between trees and different mycorrhizal fungi, i.e., arbuscular mycorrhizal (AM) vs. ectomycorrhizal (EM) association, modulate scale‐dependent DBRs. We hypothesized that in soil‐heterogeneous forests with a mixture of AM and EM tree species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 111 publications
0
14
0
2
Order By: Relevance
“…In this study, we have further found that the majority of tree species were more abundant in soil with higher levels of inorganic P, and quadrats with higher organic P sustained many fewer sapling species (Figure S16). Hence, the distinct effects of inorganic and organic P on community stability could be explained by the soil-related mycorrhizal dominance mechanism (Mao et al, 2023) stability (Figures 4b and 6). We found that average population stability had a significantly positive relationship with species diversity, which is opposite to the theoretical prediction by Lehman and Tilman (2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we have further found that the majority of tree species were more abundant in soil with higher levels of inorganic P, and quadrats with higher organic P sustained many fewer sapling species (Figure S16). Hence, the distinct effects of inorganic and organic P on community stability could be explained by the soil-related mycorrhizal dominance mechanism (Mao et al, 2023) stability (Figures 4b and 6). We found that average population stability had a significantly positive relationship with species diversity, which is opposite to the theoretical prediction by Lehman and Tilman (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, many previous studies have reported that AM tree dominance would contribute to higher tree diversity, and ECMdominated plant communities tend to be less diverse than AMdominated communities across local and geographic scales (Gerz et al, 2016;Mao et al, 2023). Four mechanisms, including access to organic nutrients, accumulation of organic material and allelopathic compounds, and positive plant soil feedback, act synergistically in ECM-dominated plant communities to maintain community monodominance over multiple generations (Johnson et al, 2023;Tedersoo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While EM tree species generally benefit from greater nitrogen mobilization from organic matter and enhanced organic and inorganic resource uptake (32), trees associated with AM fungi mainly benefit from greater uptake of less mobile nutrients such as phosphorus (26)(27)(28)(29). Mycorrhizal associations with AM or EM fungi are known to influence tree productivity differently (33)(34)(35). For instance, Deng et al (36) found that differences in nutrient acquisition strategies affect the direction of BPRs, with positive effects of tree species richness on AM tree productivity but negative effects for EM trees.…”
Section: Introductionmentioning
confidence: 99%
“…While EM tree species generally benefit from greater nitrogen mobilisation from organic matter and enhanced organic and inorganic resource uptake (32), trees associated with AM fungi mainly benefit from a greater uptake of less mobile nutrients such as phosphorus (26,29). Mycorrhizal associations with AM or EM fungi are known to influence tree productivity differently (33)(34)(35). For instance, Deng et al (2023) found that differences in nutrient acquisition strategies affect the direction of BPRs, with positive effects of tree species richness on AM tree productivity, but negative effects for EM trees (36).…”
Section: Introductionmentioning
confidence: 99%